The impact of inappropriate use of short acting beta agonists in asthma. (October 2017) - FitzGerald, J. Mark; Tavakoli, Hamid; Lynd, Larry D.; Al Efraij, Khalid; Sadatsafavi, Mohsen
Abstract: Background: Inappropriate use of short-acting beta-agonists (SABA) has been associated with increased morbidity and mortality in asthma. However, the extent and pattern of SABA use have changed significantly over recent years. The outcomes in patients who are contemporarily receiving inappropriate doses of SABA have not been evaluated. Methods: We used population-based administrative health data from British Columbia (BC), Canada, to create a cohort of asthma patients aged 14 to 55. The exposure of interest was inappropriate use of SABA with any given 12-month period, as defined and validated previously. The primary outcome was asthma-related hospitalization in the following three-month period; secondary outcomes were asthma-related emergency department (ED) visits, asthma-related intensive care unit (ICU) admissions, and asthma-attributable costs. Results: A total of 343, 520 individuals contributed 2, 127, 592 patient-years of follow up. Of these, in 190, 546 patient-years (7.7%) SABAs were used inappropriately. Inappropriate use of SABAs in any given year was associated with a 45% (odds ratio (OR) = 1.45, 95%CI 1.26–1.66) increase in the risk of asthma-related admissions in the following three-month period. Similarly, inappropriate use of SABA was associated with 25% (OR = 1.25, 95% CI 1.18–1.33) increase in the risk of asthma-related ED visits. The association with ICU admissions was not statistically significant. Inappropriate use of SABA was associated with a 6% (relative rate [RR] = 1.06, 95% CI = 1.04–1.08) increase in total-asthma-related costs. Conclusions: Inappropriate use of SABA continues to be problematic in a significant minority of asthma patients and is associated with an increased health care utilization and risk of adverse outcomes. Highlights: Evidence on the relationship between inappropriate SABA use and outcomes in contemporary asthma patients is lacking. Identifying the consequences of inappropriate use of SABA is important as it is a preventable source of burden. Inappropriate use of SABA continues to be associated with a significant increased morbidity and health related costs.